2018
DOI: 10.2337/ds18-0019
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health–Supported Lifestyle Change Programs to Prevent Type 2 Diabetes

Abstract: IN BRIEF Type 2 diabetes can be prevented or delayed in people with prediabetes through participation in an intensive lifestyle change program (LCP), particularly one based on the Diabetes Prevention Program research study. Digital health offers opportunities to extend the reach of such LCPs and possibly improve on these programs, which traditionally have been delivered in person. In this review, we describe the current state of evidence regarding digital health–supported LCPs and discuss gaps in research and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Virtual lifestyle change programs have shown benefits in terms of weight loss for a broader population with prediabetes and may be particularly attractive to women with young children and/or time constraints. 28 We found that even women with a postcollege degree who presumably have higher household incomes were only theoretically willing to pay approximately onethird of the ''true'' cost of providing the DPP curriculum. Efforts to engage women with a GDM history in diabetes prevention, including SDM, will only be successful if insurance plans, workplaces, or other stakeholders with an interest in diabetes prevention continue to cover most of the up-front cost of the DPP for this high-risk population.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Virtual lifestyle change programs have shown benefits in terms of weight loss for a broader population with prediabetes and may be particularly attractive to women with young children and/or time constraints. 28 We found that even women with a postcollege degree who presumably have higher household incomes were only theoretically willing to pay approximately onethird of the ''true'' cost of providing the DPP curriculum. Efforts to engage women with a GDM history in diabetes prevention, including SDM, will only be successful if insurance plans, workplaces, or other stakeholders with an interest in diabetes prevention continue to cover most of the up-front cost of the DPP for this high-risk population.…”
Section: Discussionmentioning
confidence: 72%
“…Virtual lifestyle change programs have shown benefits in terms of weight loss for a broader population with prediabetes and may be particularly attractive to women with young children and/or time constraints. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Similar to in-person programs, digital DPPs have been tested in workforce populations, and have shown comparable clinical performance to in-person programs. 16,17 The economic value of traditional, group-based, in-person DPPs has been demonstrated in cost-effectiveness and health care cost saving studies, with estimates of savings in the range of US$3000+ within 3 years. [18][19][20] However, very few cost analyses of workplace-based DPPs have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to in-person programs, digital DPPs have been tested in workforce populations, and have shown comparable clinical performance to in-person programs. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…There is some existing evidence that suggests that technology can help support weight management in people living with nondiabetic hyperglycemia [10] or T2DM [11]. The Diabetes Prevention Recognition Program in the United States recognizes more than 120 organizations delivering lifestyle change programs through digital or remote channels.…”
Section: Introductionmentioning
confidence: 99%